ENVIRONMENTAL EDUCATION, SUSTAINABILITY AND GREEN CONSUMPTION IN SMALL BUSINESS IN THE WESTERN AMAZON - Campos, Waleska Yone Yamakawa Zavatti; São Pedro Filho , Flávio de; Rodrigues , Martius Vicente Rodriguez y; Rosa, Luciana Aparecida Barbieri da; Martins-Rodrigues, Maria Carolina; Cohen, Marcos (Revista GESTO: Revista de Gestão Estratégica de Organizações, 2025)
This research aims to prepare a study on environmental education in the face of formal and informal actions to promote sustainability, consumption, and green behavior in small businesses in the Western Amazon. To achieve the proposed objective, the following were listed as specific objectives: (I) to analyze, through descriptive statistics, the perception of managers and employees about environmental education, sustainability and green consumption at the individual and organizational levels; (II) to investigate the correlation and association between the perception of sustainability, environmental education and green consumption. The study is justified by the environmental impacts generated by the performance of the food company and considers the possibility of contributing to the promotion of environmental education in smaller organizations, inducing good practices for the necessary environmental changes. The methodology employed descriptive statistics, Pearson’s correlation analysis and multiple linear regression. The results show that environmental education, environmental sustainability, and green consumption are correlated constructs. It was also found that environmental education and environmental sustainability are positively related to green consumption. This discovery brings important information to individuals, governments, and organizations in promoting green consumption.